2022
DOI: 10.1088/1361-6528/ac9abe
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and localized flat band in the WSe2/MoSe2 heterobilayer

Abstract: Nearly localized moiré flat bands in momentum space, arising at particular twist angles, are the key to achieve correlated effects in transition-metal dichalcogenides. Here, we use angle-resolved photoemission spectroscopy (ARPES) to visualize the presence of a flat band near the Fermi level of van der Waals (vdW) WSe2/MoSe2 heterobilayer grown by molecular beam epitaxy. This flat band is localized near the Fermi level and has a width of several hundred meVs. By combining ARPES measurements with density functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 70 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Depending on stacking order, interlayer distance, or twist angle, theoretical studies come to different conclusions about whether the valence band maximum lies either at the Γor the K-valley 44,[46][47][48][49] . Interestingly, even experimental ARPES studies come to different conclusions: Whereas one of the first reported measurements claims that the Γ-valley lies below the K-valley 76 , a more recent measurement claims the opposite 77 . As we cannot conduct ARPES measurements on the devices with a top hexagonal boron nitride (hBN) layer (see Fig.…”
Section: Deviation From the Expected Type-ii Band Alignmentmentioning
confidence: 99%
“…Depending on stacking order, interlayer distance, or twist angle, theoretical studies come to different conclusions about whether the valence band maximum lies either at the Γor the K-valley 44,[46][47][48][49] . Interestingly, even experimental ARPES studies come to different conclusions: Whereas one of the first reported measurements claims that the Γ-valley lies below the K-valley 76 , a more recent measurement claims the opposite 77 . As we cannot conduct ARPES measurements on the devices with a top hexagonal boron nitride (hBN) layer (see Fig.…”
Section: Deviation From the Expected Type-ii Band Alignmentmentioning
confidence: 99%
“…In addition to CVD, twist angles may be generated between layers grown sequentially by molecular beam epitaxy (MBE). Many studies have revealed moiré patterns in MBE grown stacks, originating from lattice mismatch and arbitrary rotation between layers. For example, in a recent study, Khalil et al grew WSe 2 /MoSe 2 heterobilayers on top of a graphene substrate by MBE and found coexistence of domains with arbitrary interlayer twist angles up to 4°, leading to a flat band observed by angle-resolved photoemission spectroscopy. As with CVD, control of the interlayer twist during MBE growth of stacked layers would greatly advance the scalability of moiré based heterostructures …”
Section: Stacking Order Engineering Enabled By Interlayer Twistmentioning
confidence: 99%